Design and Functional Test of Transistor Inverter Based on Polyvinyl Alcohol and Graphene Oxide Electrolyte. Issue 1 (18th October 2022) - Guo, Liqiang; Wang, Weilin; Li, Zhiyuan; Dong, Qian; Han, Hui; Zhang, Zhongqiang; Cheng, Guanggui; Ding, Jianning; Xue, Qing
Abstract : Eco‐friendly "green" electronics are attracting increasing interest in recent years. For example, neural prostheses, nerve implants, drug delivery devices, and diagnostic electronics, as well as some green materials (paper, silk, and polysaccharides) with bioabsorbable and biocompatible transistors, load inverters, and other devices. Here, biodegradable polyvinyl alcohol (PVA)/graphene oxide (GO) electric double‐layer (EDL) transistors are prepared on glass substrates. PVA film treated with GO solution is used as a gate dielectric. Oxide EDL transistors show good performance. A resistive load inverter is also constructed, which shows full swing characteristics and high voltage gain at low operating voltage. The waveform conversion is realized, including the conversion from sine wave to rectangular wave, and the conversion from noise signal to two‐bit output. In addition, PVA/GO transistors can be easily dissolved in water. The proposed PVA/GO oxide transistors may have potential applications in "green" portable devices. Abstract : Biodegradable polyvinyl alcohol and graphene oxide (PVA/GO) electric double‐layer (EDL) transistors are prepared on glass substrates, a resistive load inverter is also constructed, which shows full swing characteristics and high voltage gain at low operating voltage. The proposed PVA/GO oxide transistors may have potential applications in "green" portable devices.